Bison as ecosystem engineers: impacts on tallgrass prairie soil, plant communities, and microbial assemblages - Bookout, Bess (My University, 2025)
The widespread conversion of North American grasslands to agriculture, coupled with the replacement of native megagrazers, primarily bison (Bison bison), has limited our understanding of bison’s ecological roles. This dissertation investigates how bison, through both keystone herbivory and ecosystem engineering, influence tallgrass prairie in ways that differ from cattle. In Chapter 2, I used a 30-year landscape-scale experiment on fire and grazing to show that grazing increased plant species richness, altered community composition, and increased phylogenetic diversity compared to annually burned, ungrazed prairie. Bison tended to change plant communities more than cattle, though management differences obscure whether these differences are due to the grazer species or aspects of how each species is managed. However, there is one large difference between the two grazers: bison create wallows and cattle do not. In Chapter 3 and 4, I examined the effects of wallows on soil, plant communities, and microbial assemblages compared to non-wallowed bison-grazed and cattle-grazed prairie. I found that wallows had lower nutrient availability, higher salt concentrations, and distinct microbial and plant communities. Some wallows are able to hold water for weeks with consistent rainfall and thus act as ephemeral wetlands, supporting amphibians, aquatic invertebrates, and other organisms. Over time, bison naturally abandon wallows, a process we mimicked by creating exclosures around wallows. We found that unique communities also become established in these transient micro-habitats. Wallows, and their resulting differences in soil physiochemistry and hydrology, increase beta-diversity of soil microbes without decreasing alpha diversity. Bison and their behaviors, especially wallowing, act as important drivers of grassland heterogeneity, underscoring the importance of their reintroduction for restoring ecosystem function and resilience.
Keywords: Grassland ecology; Bison; Wallows; Microbial ecology; Plant communities; Rewilding